Design, synthesis and biological evaluation studies of novel anti-fibrosis agents bearing sulfoxide moiety. (1st December 2022) - Jiao, Shixuan; Huang, Wanqiu; Cao, Zhijun; Chen, Ya; Chen, Siliang; Yang, Zhongcheng; Wang, Wenxin; Yao, Huixin; Wang, Xuekun; Li, Zheng; Zhang, Luyong
Graphical abstract: Through structural modification and fragment hybridization of KRL507-031, an anti-fibrotic drugs compd. 1 was identified, which significantly improve fibrosis and reduce collage content in the CCl4 -induced liver fibrosis mice model and bleomycin-induced pulmonary fibrosis mice model. Highlights: Compd.1 be able to dose-dependently down-regulate ACTA2 and CTGF mRNA levels in human hepatic stellate cells (LX-2) treated with TGF-β. Compd.1 significantly improve fibrosis and reduce collage content in the CCl4-induced liver fibrosis mice model and bleomycin-induced pulmonary fibrosis mice model. Compd.1 is identified as a promising candidate for anti-fibrosis, and its antifibrotic activity is superior to pirfenidone. Our study extended chemical space, which might help us to explore better anti-fibrotic drugs. Abstract: Fibrosis, a chronic disease with high morbidity and mortality, is mainly characterized by excessive accumulation of extracellular matrix (ECM). At present, pathogenesis of fibrosis is incompletely understood, and there is an urgent need to develop safe and effective drugs. In this study, we designed and synthesized a series of novel small-molecule compounds through structural modification and fragment hybridization. Among them, a potential anti-fibrosis drug compd.1 was founded to be able to dose-dependently down-regulate ACTA2 and CTGF mRNA levels in human hepatic stellate cells (LX-2) treated with TGF-β. In addition, compd.1 significantly improved the bridging fibrosis and collagen content in the CCl4 -induced liver fibrosis mice model. Moreover, compd.1 reduced lung inflammation and fibrotic area in bleomycin-induced pulmonary fibrosis mice model. These findings suggested that compd.1 is a promising candidate for further anti-fibrosis researches, and extended chemical space might help us to explore better anti-fibrosis drug.